2016
DOI: 10.17261/pressacademia.2017.356
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-performing loans of deposit banks in Turkey

Abstract: This study empirically analyzes the factors that determine the non-performing loans (so-called bad loans) of 20 deposit banks in Turkey for 2006-2012 period using panel data analysis method. The analysis results reveal that solvency, profitability, credit quality, diversification, economic growth and the recent financial crisis are essential indicators of non-performing loans rate in Turkish banking sector. More specifically, greater profitability and revenue diversification significantly lowers non-performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
4
13
0
3
Order By: Relevance
“…Therefore, inefficiency as a proxy for bad management leads to poor screening and poor quality of loans and increases Turkish banks' NPLs. It is further observed that banks with higher noninterest income share have lower credit risk, a result consistent with Hu et al, (2007), Louzis et al, (2010) and Isik & Bolat (2016). Hence, diversified activities and different revenue sources enable banks to refrain from risky borrowers and decrease the amount of NPLs.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, inefficiency as a proxy for bad management leads to poor screening and poor quality of loans and increases Turkish banks' NPLs. It is further observed that banks with higher noninterest income share have lower credit risk, a result consistent with Hu et al, (2007), Louzis et al, (2010) and Isik & Bolat (2016). Hence, diversified activities and different revenue sources enable banks to refrain from risky borrowers and decrease the amount of NPLs.…”
supporting
confidence: 84%
“…Hence, diversified activities and different revenue sources enable banks to refrain from risky borrowers and decrease the amount of NPLs. Finally, it is observed that banks with higher loan loss provisions to net interest revenue have a higher NPLs ratio, which is consistent with Hasan & Wall (2004), Boudriga et al (2009) and Isik & Bolat (2016). Therefore, the higher amount of loan loss provisions indicate that risk is not properly counterbalanced by higher margins and therefore banks face increased credit risks.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Houston et al (2010), Büyükkarabacak and Valev (2012), Jappelli and Pagano (2002), Djankov et al (2007), Giannetti and Jentzsch (2013) and Beck et al (2014) use all of these economic indicators together or separately. And also papers (Jiménez & Saurina, 2006;Louzis et al 2012;Atanasijević and Božović, 2016;Fofack, 2005;Salas & Saurina, 2002;Isik & Bolat, 2016) exploring the causes of non-performing loans analyzied GDP growth rate. Unemployment rate (UNEMP) is the broadest indicator of economic activity as reflected by the labor market and usually high values point to inefficiencies in resource allocation (www.worldbank.org).…”
Section: Macroeconomic Factorsmentioning
confidence: 99%
“…Atanasijević and Božović (2016) found that exchange rate, GDP growth rate and loan size induce non-performing loans in Serbian banks. Yağcılar and Demir (2015) and Isik and Bolat (2016) explain the main determinants of non-performing loan in the Turkish banking sector by bank-specific and macroeconomic variables. Findings of Cifter, Yilmazer and Cifter (2009) reveal a relationship between sectorial production cycle and sectorial non-performing loans in the Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%